Whole-body MRI for metastases screening: a preliminary study using 3D VIBE sequences with automatic subtraction between noncontrast and contrast enhanced images - Thomson, Vivien; Pialat, Jean-Baptiste; Gay, Frédéric; Coulon, Agnès; Voloch, Alain; Granier, Anne; Guérin, Jean-Claude; Viallon, Magalie; Berthezene, Yves (American journal of clinical oncology, 2008)
To evaluate 3D Volumetric Interpolated Breath-hold Examination (VIBE) whole-body MRI (WB-MRI) acquisition for the metastases staging. Thirty-two consecutive patients with solid tumor were examined from head to feet before and after contrast injection. An automatic subtraction occurred between the 2 series of images. WB-MRI was compared with conventional staging techniques (CT, scintigraphy, brain MRI, and whole-body PET in 4 cases). WB-MRI and the reference techniques depicted metastases in 25 patients. WB-MRI depicted more bone lesions in the spine, pelvis, skull, femur, and tibia, whereas scintigraphy detected more rib lesions. WB-MRI depicted 27 cerebral metastases, whereas brain MRI depicted 40 cerebral metastases. WB-MRI depicted a total of 8 hepatic metastases, 8 adrenal lesions, and conventional staging 7 hepatic metastases and 10 adrenal lesions. WB-MRI examination depicted lung metastases in 10 patients, and CT examination in 13 patients. The results of this study indicate that WB-MRI is a feasible and promising technique for tumor staging.